2022
DOI: 10.3389/fmed.2022.839088
|View full text |Cite
|
Sign up to set email alerts
|

The Validation of Deep Learning-Based Grading Model for Diabetic Retinopathy

Abstract: PurposeTo evaluate the performance of a deep learning (DL)-based artificial intelligence (AI) hierarchical diagnosis software, EyeWisdom V1 for diabetic retinopathy (DR).Materials and MethodsThe prospective study was a multicenter, double-blind, and self-controlled clinical trial. Non-dilated posterior pole fundus images were evaluated by ophthalmologists and EyeWisdom V1, respectively. The diagnosis of manual grading was considered as the gold standard. Primary evaluation index (sensitivity and specificity) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The accuracy of AI-based telemedicine screening was extracted from published studies specific to the AI-assisted screening model conducted in Shanghai based on the current dominant architecture of convolutional neural networks (Multimedia Appendix 10) [25]. Briefly, the sensitivity was 80.47% (95% CI 75.07%-85.14%) and the specificity was 97.96% (95% CI 96.75%-98.81%) for STDR [25]. In our screening program, 2 experienced ophthalmologists were employed to make the diagnoses based on the retinal images.…”
Section: Screening Accuracymentioning
confidence: 99%
“…The accuracy of AI-based telemedicine screening was extracted from published studies specific to the AI-assisted screening model conducted in Shanghai based on the current dominant architecture of convolutional neural networks (Multimedia Appendix 10) [25]. Briefly, the sensitivity was 80.47% (95% CI 75.07%-85.14%) and the specificity was 97.96% (95% CI 96.75%-98.81%) for STDR [25]. In our screening program, 2 experienced ophthalmologists were employed to make the diagnoses based on the retinal images.…”
Section: Screening Accuracymentioning
confidence: 99%
“…Finally, the results showed that the accuracy, sensitivity, and specificity of the model on the EyePACS-1 dataset were 0.899, 0.882, and 0.913, respectively, and the accuracy, sensitivity and specificity of the model on the Messidor-2 dataset were 0.918, 0.902, and 0.930, respectively. To assist DR classification, Zhang W. F et al (2022) developed an AI classification model based on ResNet-34 and Inception-v3 and used 1,089 fundus images to train and test the model. After testing, the AUC of the model was 0.958 and the kappa score was 0.860.…”
Section: Application Of Artificial Intelligence In Retinal Vascular D...mentioning
confidence: 99%
“…They used the APTOS 2019 dataset to evaluate the performance of the AI model, and the final results showed that the DR classification model's accuracy was as high as 0.98. Similarly, Zhang et al [60] constructed an AI hierarchical model by ResNet-34 and Inception-V3 networks, which can automatically divide DR into five levels: no DR, mild DR, moderate DR, severe DR, PDR. In addition, they collected 1089 color fundus photographs to evaluate the performance of the AI model.…”
Section: Ai-assisted Dr Diagnosismentioning
confidence: 99%